New approaches to thyroid hormones and purinergic signaling - Silveira, Gabriel Fernandes (2013)
It is known that thyroid hormones influence a wide variety of events at the molecular, cellular, and functional levels. Thyroid hormones (TH) play pivotal roles in growth, cell proliferation, differentiation, apoptosis, development, and metabolic homeostasis via thyroid hormone receptors (TRs) by controlling the expression of TR target genes. Most of these effects result in pathological and physiological events and are already well described in the literature. Even so, many recent studies have been devoted to bringing new information on problems in controlling the synthesis and release of these hormones and to elucidating mechanisms of the action of these hormones unconventionally. The purinergic system was recently linked to thyroid diseases, including enzymes, receptors, and enzyme products related to neurotransmitter release, nociception, behavior, and other vascular systems. Thus, throughout this text we intend to relate the relationship between the TH in physiological and pathological situations with the purinergic signaling.